IAQ analysis of Portuguese residential buildings - Silva, Sandra Monteiro (2012)
In average, man spends about 90% of the time inside enclosed spaces, in both residential and office buildings, exposed to consistently higher concentrations of air pollutants than outdoors, which has led to the increased rate of allergies and asthma incidences. In the last decade, public and governmental awareness on indoor air quality (IAQ) has been growing. Portugal implemented the National Building Energy and Indoor Air Quality Certification System in 2006 which imposes periodic IAQ audits for office buildings. However, in residential buildings, the only normative imposition related to IAQ is the obligation of a minimum air change rate of 0.6 h-1. The number of potential pollutants inside residential buildings is significant, and even low concentration levels can cause health problems if combined effects are considered. Additionally, the inhabitants’ behaviour can have a significant impact on IAQ. Therefore, the assessment of IQA is very important. This paper presents the application of the IAQ audit methodology, defined by the Portuguese legislation for office buildings, to residential buildings. The concentration of suspended particles, carbon dioxide, carbon monoxide, ozone, formaldehyde and total volatile organic compounds were measured as well as the air change rate. A standard questionnaire was delivered to the inhabitants to also obtain a subjective assessment of the IAQ. The goal of this study was to verify the IAQ conditions inside the Portuguese residential buildings and to establish a comprehensive IAQ audit approach for residential buildings. The results gathered will also be used to identify the main problems of Portuguese residential building stock and to develop guidelines to improve IAQ in residential buildings.